Effect Of Quality Of Service, Reputation And Value Of Service Higher Education On Student Satisfaction - Darmawan, Kusnanto (Jurnal Ilmu Manajemen Advantage, 2017)
This study aims to measure the level of student satisfaction on dimensions of quality education services either partially or partial. Dimensions of the quality of education services consist of tangible, reliability, responsiveness, assurance and empathy. Respondents were 60 students STIE Widya Gama Lumajang. Data analysis technique used is multiple linear regression analysis, by first testing the research instrument, namely the validity and reliability. The results showed that partially there are two variables that affect student satisfaction is assurance and empathy, while simultaneously dimensions of service quality education consisted of five variables affect the student satisfaction. 52.9% student satisfaction can be explained by the independent variables are physical evidence, reliability, responsiveness, assurance, empathy, while the remaining 47.1% of student satisfaction is influenced by other variables not examined in this study